New Structural Economics : A Framework for Rethinking Development - Lin, Justin Yifu (World Bank, 2013)
As strategies for achieving sustainable growth in developing countries are re-examined in light of the financial crisis, it is critical to take into account structural change and its corollary, industrial upgrading. Economic literature has devoted a great deal of attention to the analysis of technological innovation, but not enough to these equally important issues. The new structural economics outlined in this paper suggests a framework to complement previous approaches in the search for sustainable growth strategies. It takes the following into consideration.